Effect of the kinesio taping application method for the activation and strength of gastrocnemius muscles in healthy adults (Research, Society and Development, 2022)
The objective of this study was to verify the effect of kinesio-taping (KT) application of the origin for muscle insertion (O>I) and insertion for muscle origin (I>O) in healthy participants, through surface electromyography and peak torque of gastrocnemius muscles. A total of 69 participants with an average age of 22.9±5.2 years were evaluated, 41 women with an average age of 22.0±5.1 years, BMI 25.1±4.6 kg/m2, and 28 men with an average age of 22.0±5.1 years, BMI 23.1±3.3 kg/m2, randomized under three conditions: O>I, I>O and no KT (control), repeated three times with five-minute rest between sessions. The peak torque of the gastrocnemius lateral (GML) and medial (GMM) muscles was evaluated at speeds 30º/s 60º/s 120º/s and muscle activity through surface electromyography. Repeated-measurement ANOVA showed effect only on the variable speed (F=767,1; pI or I>O muscular, did not alter the muscle recruitment or contribute to the increase in peak torque performance during the three speeds.